The Meanings of the Suspicious Adjective (Verb) in the Noble Qur’an - Khalaf , Abdul Khaleq (Islamic Sciences Journal, 2023)
ABSTRACT Praise be to Allah, and prayers and peace be upon our Prophet Muhammad, his family and companions, and those who are guided by his guidance, and after:This is a modest study of the meanings of the suspicious adjective (verb) in the Holy Qur’an, the purpose of which is to identify the words that came on this formula, and to clarify their meanings in the lexicon, and the verses at which they have been mentioned and their significance in the context at which they were mentioned, to find out the truth of the rule set by grammarians and linguists that what came in this formula is in the symptoms, aches, and internal diseases, and what is close to it in meaning in terms of distress and hardship, and in agitation and lightness.